Pathfinders of the West: being the thrilling story of the adventures of the men who discovered the great Northwest, Radisson, La Vérendrye, Lewis and Clark - Laut, Agnes C., 1871-1936. (New York, The Macmillan company: London, Macmillan & co., ltd., 1922)
--pt.1. Pierre Esprit Radisson.--pt.2. The search for the western sea, being an account of the discovery of the rocky Mountains, the Missouri uplands, and the valley of the Saskatchewan.--pt.3. Search for the Northwest passage leads Samuel Hearne to the Arctic circle and athabasca region.--pt.4. First across the Rockies - How Mackenzie crossed the northern Rockies and Lewis and Clark were first to cross from Missouri to Columbia. Mode of access: Internet.